Analysis of the Maximum Volume of Production in Cement Production Enterprises in Uzbekistan - Pardayevich, Klichev Bakhtiyor (Research Parks Publishers, 2023)
This article covers the issues of implementation of analytical work on the contents of the indicators representing the volume of production developed by the author and their interrelationships. Based on the data of Ohangarontsement JSC, the leading enterprise producing cement products in Uzbekistan, the procedure for calculating the maximum volume of production, the theoretical and practical aspects of the indicators determined by mutual ratios of the proposed indicators representing the volume of production are explained. In the performed calculations, relative indicators, data grouping, logical analysis, index and small number methods were used, calculations were made and analytical solutions were given.